Efektivitas Pembelajaran Paikem Card Sort Terhadap Hasil Belajar Kelas IV SD Negeri Betokan 1 - Shikha Hidayaturrokhmah; Qoriati Mushafanah; Khusnul Fajriyah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The background that underlies this research is the low learning outcomes of  IV Thematic Theme 8 learning at SD Negeri Betokan 1 Demak. This is because the teacher in teaching still uses the lecture method so that students are bored to follow the lesson. The purpose of this study was to determine the use of the PAIKEM learning model type Card Sort Effectively on student learning outcomes in thematic learning Class IV Theme 8 The Area Where I Live, SD Negeri Betokan 1 Demak. This research uses quantitative research, the research design used is Pre Experimental Design, while the Pre Experimental Design design used is One-Group Pretest-Posttest Design. The results of the final analysis that was carried out using the t-test showed the results of tcount > ttable, namely 4.858 > 2.080. Then for the mastery of learning the Classical Posttest, the results obtained were 77.27%. So the conclusion is that H0 is rejected and Ha is accepted so that it shows that the Card Sort type PAIKEM learning model is effective for thematic learning outcomes of fourth grade students at SD Negeri Betokan 1 Demak.